Stiffness and strength degradation of damaged truss core composites. (July 2015) - Siska, Filip; Tawfeeq, Arwa F.; Dlouhy, Ivo; Barnett, Matthew R.
Abstract: Truss core laminates display stiffness and strength/density ratios superior to those seen in foam cored laminates. However, this superiority is held only for ideal shaped struts. If the truss core is damaged, its performance rapidly decreases towards that of a foam. The present study investigates the stiffness and strength degradation with imposed core deformation/damage. This is done for a pyramidal core structure made by electro-discharge machining from AA5083 alloy. The experiments are compared with finite element predictions. The effect of the strain rate sensitivity is studied by performing the tests at different temperatures and by FE simulations with different material data sets. The results show reasonable agreement between experiments and modeling. The stiffness of a damaged truss core rapidly degrades and reaches the performance levels seen in foams after ≈8% of deformation. The results show that a high strain rate sensitivity significantly influences post-buckling core behavior and is able to decrease the stiffness and strength degradation rate.